Electroenzymatic CO2 Reduction Using Formate Dehydrogenase: Direct and Mediated Catalysis - Navendu Paul; Isabel Moura; Luísa B. Maia; Cristina M. Cordas; Jose J. G. Moura (ChemElectroChem)
The electrocatalytic reduction of carbon dioxide (CO2) to formate by the enzyme formate dehydrogenase (FDH) makes use of the enzyme's observed reversibility, offering a promising strategy for the mitigation of CO2 and the production of value‐added compounds. To enhance the catalytic potential of Desulfovibrio desulfuricans FDH (DdFDH), a range of artificial and natural redox cofactors is investigated using electrochemical methods. These studies included direct (nonmediated) conditions and mediated conditions employing viologens (methyl and benzyl viologens), and small heme proteins (cytochromes). Methyl viologen acts as an efficient mediator for CO2 reduction, achieving a very high current density of 216 μA cm−2. The studies of the different small proteins, namely cytochrome split‐soret (cyt SS), cytochrome c3 (cyt c3), and cytochrome c552 (cyt c552), allow the identification of the potential natural physiological partners. These isolated cytochromes, from the same organism, are electrochemically characterized, from which detailed redox processes are determined and later used as mediators to explore DdFDH catalytic activity in both formate oxidation and CO2 reduction. Best results are attained with cytochrome cyt SS and cyt c3, increasing the electrocatalytic activity for formate oxidation by 7.5 times and 5.8 times, respectively.